A comparative study on the evolution of compressible vortex ring generated from a short driver section shock tube. (8th September 2020) - Dey, Santanu; Murugan, T; Chatterjee, Dipankar
Abstract: The compressible vortex ring emanating from an ultra-short driver section shock tube is simulated using Euler and Navier–Stokes solvers for a diaphragm pressure ratio of 8.4. The numerical results are compared with smoke flow visualization experiments performed in a shock tube. Here the main focus is to compare the vortex ring evolution during its self-sustained motion as many researchers studied the vortex ring dynamics during its formation and growth stage. It is observed that the formation and interaction of Kelvin–Helmholtz (K-H) vortices generated at the trailing jet make the flow distinct in the solvers and experiments though the shock cell structures, embedded shock, and counter-rotating vortices are similar. Surprisingly in simulations, the vortex ring has regained its compact structure after its strong interactions with K-H and counter-rotating vortices. Whereas, it becomes a turbulent structure during its self-sustained motion in experiments. Further, the vortex ring simulated through a viscous solver moves downstream with a higher translational velocity compared to the inviscid solver at the later stage. The translation velocity of the vortex ring is the least in experiments and it may be attributed to the strong turbulent viscosity compared to the physical viscosity.